Reconstitution de gestes funéraires - David Peressinotto; Bruno Maureille; Yves Lecointe; Francis Geus (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In a temperate environment, during the excavation of burials, it is very rare to find the remains of shroud pieces. At the opposite, the very dry climate of the Middle Nubia can explain by itself the exceptional conservation of soft parts of the human body (hair, nails, brain, muscular fibres, human coprolithes) as it is frequently found at the North necropolis (SN) of the Saï island (Northern Province, Sudan). In a post X-group and ante-Muslim burial (T. 176), the excavation has allowed the discovery of a very young individual still wrapped in a shroud. It has been possible to reconstruct the shape of the shroud, the way in which it was wrapped and fixed around the body. This has allowed us to present the hypothesis that the shape of the shroud and the way to attach it have had a voluntary influence in the final position of the child in the pit, i. e. a dorsal decubitus of the body with the head hyper-flexed on the top of the trunk. Then, even if one side of the tissue of the shroud has been tear without care, its final shape is voluntary and implies a well defined funeral practice for such a child. In a Nubian archaeological context, such a practice is described for the first time —for the post X Group period in Sudan— at the Saï Island. Moreover, the limited extension of the excavated archaeological surface of this necropolis has allowed the discovery of other individuals (adults, juveniles) with important and also well preserved pieces of tissues or shrouds. Then, the taphonomical as well as the paleobiological potentialities of this necropolis seem to be very important.